2007
DOI: 10.1158/0008-5472.can-07-0077
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Dynamics of EGFR Activity and Antiglioma Therapies In vivo

Abstract: Many altered pathways in cancer cells depend on growth factor receptors. In primary malignant gliomas, the amplification/ alteration of the epidermal growth factor receptor (EGFR) has been shown to play a significant role in enhancing glioma burden. In an effort to dissect the role of EGFR expression in glioma progression in vivo and evaluate targeted therapies for gliomas, we have genetically engineered glioma cells to visualize the dynamics of EGFR and targeted therapies in real time in vivo. Using engineere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…To study whether Smad-dependent transcriptional pathways were active in the bone metastasis, we used a functional imaging system using a xenograft model. Dual-color bioluminescence imaging is useful for monitoring two molecular events in the same living animal (Arwert et al, 2007). Using this system, we showed that TGF-b and BMP induced the Smaddependent transcriptional pathways to become active in highly bone metastatic MDA-231-D human breast cancer cells that were growing as bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…To study whether Smad-dependent transcriptional pathways were active in the bone metastasis, we used a functional imaging system using a xenograft model. Dual-color bioluminescence imaging is useful for monitoring two molecular events in the same living animal (Arwert et al, 2007). Using this system, we showed that TGF-b and BMP induced the Smaddependent transcriptional pathways to become active in highly bone metastatic MDA-231-D human breast cancer cells that were growing as bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, EGFR gene amplification is positively correlated with molecularly defined GBM subclasses, characterized by active proliferation and poor prognosis (21). Valuable preclinical information has also been obtained by modulating EGFR expression in standard serum-cultured glioma cell lines (22)(23)(24)(25) and by using these in vitro cultures for testing different therapeutic approaches (26).…”
Section: Introductionmentioning
confidence: 99%
“…13 The MAPK signaling pathway can be triggered by several different growth factors, including TGFa, that bind to the epidermal growth factor receptor (EGFR), 14 which is amplified (in 40% of cases) or over expressed (in 50% of cases) in gliomas. 15,16 At the tumor level, the progression of the tumor is determined by the spatiotemporal distribution of nutrients and signaling cues. Nutrients and bloodborn growth factors (i.e., TGFa) that trigger the activation of the MAPK signaling pathway are supplied by the vasculature.…”
Section: Introductionmentioning
confidence: 99%